2022
DOI: 10.3390/agriculture12101561
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Testcross Performance for Carotenoid Content of S2 Super Sweet Corn Lines Derived from Temperate Germplasm

Abstract: Understanding the impact of gene action and combining ability on targeted traits in a hybrid breeding program is imperative. The objective of this study was to estimate the genetic effect and combining ability of S2 super sweet corn lines on carotenoid content. Twenty S2 lines were crossed with two hybrid testers by using the line × tester mating design. Regarding parents, forty hybrids and two commercial checks were evaluated for carotenoid content across two different growing seasons between 2019 and 2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…In contrast, parents with poor GCA effects may produce hybrids with high SCA effects due to the involvement of complementary genes. Previous studies found similar findings [ 25 , 27 , 51 ]. The high × low combiner was appropriate for heterosis breeding, whereas the high × high combiner for population improvements via pedigree selection [ 23 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In contrast, parents with poor GCA effects may produce hybrids with high SCA effects due to the involvement of complementary genes. Previous studies found similar findings [ 25 , 27 , 51 ]. The high × low combiner was appropriate for heterosis breeding, whereas the high × high combiner for population improvements via pedigree selection [ 23 ].…”
Section: Discussionsupporting
confidence: 86%
“…Lutein and zeaxanthin, which are α-xanthophyll or macular carotenoids central to reducing the risk of AMD, were the predominant carotenoids found in our biofortified hybrids (37.8 and 35.3%, respectively, totaling 73.1%), followed by β-carotene (17.1%) and β-cryptoxanthin (8.7%) ( Figure 1 and Supplementary Table S2 ). Previous studies reported that about 30% of lutein or zeaxanthin was found in the F 1 hybrids evaluated [ 11 , 25 ]. However, other studies found only zeaxanthin as the major carotenoid, representing more than 50% of total carotenoids [ 15 , 18 , 23 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corn cultivars with high carotene content have been produced through plant breeding [ 223 ]. Humans who consume carotenoids through their diet have been found to improve eye health in humans and most importantly, prevent age-related macular degeneration.…”
Section: Bio-fortified Agro-productsmentioning
confidence: 99%